Gd3+ and Y3+ co-doped mixed metal oxide nanohybrids for photocatalytic and antibacterial applications. (1st February 2021) - Kannan, Karthik; Radhika, D.; Reddy, Kakarla Raghava; Raghu, Anjanapura V; Sadasivuni, Kishor Kumar; Palani, Geetha; Gurushankar, K
Abstract: Rare earth based mixed metal oxide nanohybrids have become unique and tend to show impressive performance in different fields of applications such as photocatalytic, and biological, and electrochemical systems. NiO-CGYO [nickel based yttria and gadolinia co-doped ceria, fabricated composition with a formula NiO-Ce0.9 Gd0.1 O2− δ –Ce0.9 Y0.1 O2− δ ] nanocomposite was prepared by the wet-chemical method by rare earth-based metal originators and examined for use in three applications such as electrochemical, photocatalytic and biological activity. The formation of fluorite cubic crystal structure with no secondary phase (XRD) was observed and metal-oxygen bonds (FT-IR) were revealed. SEM and EDAX analysis revealed chemically pure almost spherical nanocomposite particles with a size of 40–70 nm. The electrochemical behaviour assessed from room temperature up to 600 °C at 1.3 V in the frequency assortment from 42 Hz to 5 kHz showed maximum values of conductivity at elevated temperatures (500°C–600°C). The photocatalytic activity of the prepared NiO-CGYO nanocomposite resulted in 90% methylene blue (MB) dye degradation after 120 min. NiO-CGYO also demonstrated admirable antibacterial activity against foodborne pathogens comparable with that of the standard antibiotic (Streptomycin).